Agricultural nitrate attenuation in a small groundwater-influenced wetland system - Crossley, Leah M.; MacQuarrie, Kerry T. B.; Danielescu, Serban (Frontiers in Environmental Science, 2025)
Nitrate contamination of freshwater systems is common in agricultural watersheds, leading to human and environmental health concerns. The Bells Creek watershed, located in central Prince Edward Island (PEI), Canada, is dominated by agricultural land use and has elevated nitrate concentrations in groundwater and surface water. Beneficial Management Practices (BMPs), such as constructed wetlands, may provide a means of mitigating such contamination; however, the significance of small wetlands in regulating or attenuating nitrate in PEI has yet to be investigated. In this year-long (August 2023 – July 2024) study, the nitrate loads delivered to a small (1.2 ha) groundwater-influenced, stream-wetland system were quantified using high-frequency monitoring techniques. Results indicate that discharge variability is the primary control on the observed variability of surface and subsurface nitrate loads. The total annual nitrate load to the wetland was approximately 30,000 kg NO3-N/yr. Groundwater discharge, which bypasses the wetland riparian zone, contributed approximately 67% of the total load to the wetland. Weekly flux calculations revealed that the wetland behaved as a nitrate sink for 49 out of 52 weeks of the year. Overall, the wetland attenuated 39% of the imported annual nitrate load which, on a wetland catchment area basis, is equivalent to 21.1 kg NO3-N/ha catchment/yr. A positive, non-linear trend between the imported nitrate load and the percent change in nitrate load revealed that the wetland attenuated disproportionately more nitrate during periods of high imported loads. These findings indicate that small, constructed wetlands may be an effective component of BMPs aimed at reducing nitrate loads in agriculturally dominated watersheds like those in Prince Edward Island.